Third wave COVID-19 delta variant breakthrough infection in a Hispanic-dominant suburb of Miami, Florida: ethical dilemma and vaccination hesitancy - Sam Kara; Gavrilo Lazovic; Farah Chohan; Jannel A. Lawrence; Mahnoor Sukaina; Omoyeme Edaki; Kester Nedd (SAGE Publishing, 2022)
Background and Aims: The peak of the third wave of COVID-19 infection was in the summer (August-September) of 2021, dominated by the Delta variant. Florida was the epicenter of the third wave with more than 151,449 cases in the first week of August with a positivity rate of 20%. The purpose of this study is to identify the percentage of COVID-19 infection in vaccinated patients in a minority population in south Florida and to elucidate the relationship, if any, between demographics and breakthrough infections, the rate of vaccine hesitancy, as well as the willingness to receive the monoclonal antibody REGEN-COV for the treatment of COVID-19. Methods: This cross-sectional study was performed at the Emergency Department, Larkin Community Hospital Palm Spring Campus, located in Hialeah, the fourth largest city in Florida. Hialeah is dominated (94.7%) by Hispanics and Latinos. This city represents a cross-sectional sample of US cities in general and Florida in specific. We enrolled 127 COVID-19 PCR-positive patients. Results: The infection in vaccinated patients (breakthrough) was found to be about one in three (34%). Despite the high infection rate and mounting death toll, about 73% of our unvaccinated patients answered no to the question 'knowing the consequences of being infected with COVID-19 and the fact that you are positive, would you have chosen to be vaccinated earlier?' However, about 27% of these patients agreed to receive the vaccine and 20.5% received the monoclonal antibody REGEN-COV. Conclusions: Our study revealed that vaccine hesitancy in South Florida continues to be a major challenge, especially with the emergence of mutations including Delta plus and Omicron.